2015
DOI: 10.1016/j.ijfatigue.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of impact damage on fatigue performance of structures reinforced with GLARE bonded crack retarders

Abstract: a b s t r a c tFibre-Metal Laminates (FML) such as GLARE are of interest as bonded crack retarders (BCR) to improve the fatigue performance of aircraft structures. The degradation of the performance of the crack retarder in service if subjected to damage is a critical factor in designing with this concept. Bonded assemblies of an aluminium alloy substrate reinforced with a GLARE strap were prepared, and were subjected to low velocity impact damage onto the GLARE, with impact energies ranging from 10 to 60 J. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The fatigue damage accumulation takes place in both the aluminum layers and the fiber/epoxy composite layers, making the interpretation of the possible stiffness reduction more difficult. While preliminary experimental studies on the fatigue behavior of GLARE laminates can be found in the literature [21,22], results concerning the effects of hygrothermal conditioning on the fatigue life of GLARE laminates are limited. During the fatigue testing on GLARE laminates, fatigue crack initiation generally occurs in the aluminum layer first.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…The fatigue damage accumulation takes place in both the aluminum layers and the fiber/epoxy composite layers, making the interpretation of the possible stiffness reduction more difficult. While preliminary experimental studies on the fatigue behavior of GLARE laminates can be found in the literature [21,22], results concerning the effects of hygrothermal conditioning on the fatigue life of GLARE laminates are limited. During the fatigue testing on GLARE laminates, fatigue crack initiation generally occurs in the aluminum layer first.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…FM94 adhesive with a curing temperature of 120°C was used to bond the straps onto the substrate. The curing procedure is described in detail in Syed et al After curing, the specimens were inspected using an ultrasonic phased array (C‐scan) to ensure a defect‐free bond.…”
Section: Methodsmentioning
confidence: 99%
“…In application, curing at elevated temperature is a requirement based on aircraft operation conditions. Among various materials, the fibre‐metal laminate GLARE has been shown to be most effective owing to its low density, low residual stress arising from curing straps at elevated temperature, and improved fatigue and impact performance . In previous work, application of GLARE bonded crack retarders showed large benefit in AA2024 and AA7085.…”
Section: Introductionmentioning
confidence: 99%
“…The present paper extends the findings of the previous work [15,16] and experimentally explores the concept of GFRP reinforcement as a means of ensuring enhanced structural performance of double-lap tension bolted joint configurations in annealed and heat-strengthened glass. Whilst the technique proposed in the present paper or other similar strengthening methods are not reported in the literature for glass-bolted joints, adhesively bonded fibre-metal laminates strips have been successfully used in aircraft structures as a means of improving damage tolerance through their contributions as a bonded crack retarder [17]. Given glass is a brittle material and glass fractures in the vicinity of the bolted joints, it is expected that the crack retardation contributions of the bonded GFRP strips will enhance the structural response of the glassbolted joints.…”
Section: Introductionmentioning
confidence: 99%